Threats to the Sustainable Development of the Russian Arctic: Poverty - Elena A. KORCHAK (Arctic and North, 2020)
The modern paradigm of the theory and practice of social development is the concept of sustainable development, the emergence and spread of which was associated with the emphasis on environmental pollution and overpopulation of the planet against the background of limited natural resources. Today, sustainable development is defined as the result of the interaction of a man, the economic system, and nature at the global, national, regional, and local levels. It is expressed, to a certain extent, by economic, environmental, and social sustainability. Modern goals in the field of sustainable development are to promote green growth, rational environmental management, ensuring access to quality health and education services, and improving the well-being of the population. The latter implies, first, the reduction of multidimensional poverty, the numerous groups of social localization, i.e., disabled people, families with children, single-parent families, and ethnic minorities. The aim of the study is to assess the level and extent of poverty and its social localization in the framework of achieving sustainable development of the regions of the Russian Arctic. The relevance of the study is determined by the fact that the rates and proportions of sustainable development of the Russian Arctic depend on the qualitative state of human potential (carried by the population). The qualitative state of human potential depends on the level of well-being of the population, which determines the degree of satisfaction of needs for benefits and access to social services. Poverty as a socio-economic phenomenon creates threats of degradation of human potential. The research hypothesis is based on the understanding that poverty is a systemic factor that limits the possibilities of a high-quality reproduction of human potential and, accordingly, promising opportunities for achieving sustainable development in the Russian Arctic. The research methods were a statistical analysis of the socio-economic situation of families with children in ...